A multi‐institutional study to assess adherence to lung stereotactic body radiotherapy planning goals. Issue 8 (13th July 2015) - Woerner, Andrew; Roeske, John C.; Harkenrider, Matthew M.; Fan, John; Aydogan, Bulent; Koshy, Matthew; Laureckas, Robert; Vali, Faisal; Campana, Maria; Surucu, Murat
Abstract : Purpose: A multi‐institutional planning study was performed to evaluate the frequency that current guidelines established by Radiation Therapy Oncology Group (RTOG) protocols and other literature for lung stereotactic body radiotherapy (SBRT) treatments are followed. Methods: A total of 300 patients receiving lung SBRT treatments in four different institutions were retrospectively reviewed. The treatments were delivered using Linac based SBRT (160 patients) or image guided robotic radiosurgery (140). Most tumors were located peripherally (250/300). Median fractional doses and ranges were 18 Gy (8–20 Gy), 12 Gy (6–15 Gy), and 10 Gy (5–12 Gy) for three, four, and five fraction treatments, respectively. The following planning criteria derived from RTOG trials and the literature were used to evaluate the treatment plans: planning target volumes, PTVV 100 ≥ 95% and PTVV 95 ≥ 99%; conformality indices, CI100% < 1.2 and CI50% range of 2.9–5.9 dependent on PTV; total lung‐ITV: V 20Gy < 10%, V 12.5Gy < 15%, and V 5Gy < 37%; contralateral lung V 5Gy < 26%; and maximum doses for spinal cord, esophagus, trachea/bronchus, and heart and great vessels. Populations were grouped by number of fractions, and dosimetric criteria satisfaction rates (CSRs) were reported. Results: Five fraction regimens were the most common lung SBRT fractionation (46%). The median PTV was 27.2 cm 3 (range: 3.8–419.5 cm 3 ). For all plans: mean PTVV 100 was 94.5% (±5.6%, planning CSR: 69.8%), mean PTVV 95 was 98.1% (±4.1%, CSR: 69.5%), mean CI100% was 1.14 (±0.21, CSR: 79.1%, and 16.5% within minor deviation), and mean CI50% was 5.63 (±2.8, CSR: 33.0%, and 28.0% within minor deviation). When comparing plans based on location, peripherally located tumors displayed higher PTVV 100 and PTVV 95 CSR (71.5% and 71.9%, respectively) than centrally located tumors (61.2% and 57.1%, respectively). Overall, the planning criteria were met for all the critical structure such as lung, heart, spinal cord, esophagus, and trachea/bronchus for at least 85% of the patients. Conclusions: Among the various parameters that were used to evaluate the SBRT plans, the CI100% and CI50% were the most challenging criteria to meet. Although the CSRs of organs at risk were higher among all cases, their proximity to the PTV was a significant factor.